CFD Prediction of Heat and Fluid Flow through U-Bends using High Reynolds-number EVM and DSM Models - M. F., Ghazali; F. A., Rahim (Elsevier Ltd, 2013)
The cooling system of gas turbine blades understanding and improvement is increasing desires for computational techniques which can accurately model the flow field and heat transfer characteristics of blade cooling passage designs under realistic operating conditions. The present study discusses the comparisons between modeling and measuring gas turbine blade-cooling applications of the flow development and heat transfer in a stationary square cross-sectioned U-bend of strong curvature of Rc/D = 0.65. A turbulence model of the differential stress model (DSM) is used in combination with three different wall treatments such as a standard form of the wall function (SWF), an analytical wall function (AWF) and a numerical wall function (NWF). The combination of DSM with the numerical wall function (DSM/NWF) has improved markedly the Nusselt number predictions along the outer wall after the bend exit, but did not show any other distinctive predictive advantages over the other DSM models.